Efficacy of Quality Assurance Practices in Promoting Diversity and Inclusion In Higher Education Institutions - Kwao, Moses Paafio; Toolo, Lineo L. (International Journal of Scientific Research and Management (IJSRM), 2025)
The growing concern for QA in Ghana is driven by the rapid increase in the number of HEIs and the surge in enrolment figures, which have not been matched by a corresponding rise in resources and infrastructure. An increasingly diverse student population further complicates the quality debate in HEIs. The study aimed at exploring efficacy of QA practices in promoting diversity and inclusion in HEIs. Descriptive survey design was used for the study.  Purposive and convenience sampling technique was used in sampling 338 students from the various universities. A google form of questionnaire was designed to gather information from students of the sampled universities in Ghana. SPSS version 26 was used to perform descriptive characteristics (frequency, percentage, mean, standard deviation), and inferential statistics (Correlation analysis). The study showed moderately effectiveness of QA practices at HEIs in promoting diversity and inclusion (M=3.23, SD=1.179). The study found a disparity between public and private universities, suggesting that QA practices are more effective in promoting diversity and inclusion at public institutions. Additionally, it was found that male students, older students, and those in higher academic levels perceived QA practices as more effective in promoting diversity and inclusion within the university environment. The study recommends policy-level changes aimed at updating legislative instruments governing QA practices in HEIs. These amendments should explicitly incorporate diversity considerations to ensure QA practices are optimally effective in promoting diversity and inclusion across the higher education sector. Such proactive measures are essential for fostering environments where all students feel valued, respected, and empowered to succeed.